Russia e Polonia nella Ostpolitik dell’Unione europea - Malghin, Artem V. (Rivista di studi politici internazionali, 2022)
The Author, member of the Russian-Polish Group for difficult issues, explains his vision of the torturous relationships between Russia and Poland, and in the political context of postcommunism era he analyzes the impact of stereotypes and preconceptions that have been formed in Russia and Poland over centuries. The attention goes to Poland’s eastern policy strategies within the framework of the European Union, particularly to the Policy of Neighborhood and Eastern Partnership. The Author remains hopeful about positive developments in bilateral relations between Moscow and Warsaw.